Sosialisasi Usulan Perancangan Tata Letak Pabrik Pada PT Sari Kayu, Jakarta Timur - Hidayat, Trifenaus Prabu; Sugioko, Andre; Widawati, Enny; Silalahi, Agustinus; Wahju, Marsellinus Bachtiar; Adrian, Bryan (Jurnal Pengabdian Masyarakat Charitas, 2021)
The problem faced by PT Sari Kayu is that fluctuating production demand and high product variance make production inefficient. If the problem does not have a good factory layout, it affects material handling costs, material handling distances, and material handling time. For example, at PT Sari Kayu, there was a delay during a wrong project because the two projects were running simultaneously. The delay is due to the lack of resistance of the production floor to sudden high fluctuations in production demand. In addition, product variance is also a factor in the longer production process due to the different sequence of production processes and less supportive machine layouts. It is hoped that with the proposed layout, PT Sari Kayu will be able to face the fluctuating demand for production.